The Effect of Green Brand Knowledge and Environmental Concern on Green Purchase Intention Through Attitude Toward Green Brand in Tupperware - Mely Saputri, Abdulah; Santi Paramita, V. (Publisher Cv. Inara, 2024)
The general people are well aware of the necessity of environmental protection. Many companies have formed to operate enterprises that provide ecologically friendly items. The purpose of this study is to look at how green brand awareness and environmental concern, as mediated by attitudes toward green brands, impact green purchase intentions for Tupperware goods on the Indonesian island of Java. Descriptive, multiple regression and Sobel tests were used to analyze the data. This study included 120 respondents selected using non-probability sampling procedures. Empirical findings validate the seven specified research hypotheses. Research findings show that green brandnknowledge and environmentalcconcern influence greennpurchase intention, then attitude toward green brand does not influence greennpurchase intention, and attitude towarddgreen brandddoes notmmediate the influence of green brand knowledgeeand environmental concern on green purchase intention. It is also hoped that the results of this research will be useful in helping develop strategic policies related to the environment to increase purchasing intentions.